Tirinea de Jesús Urzagasti (1969) - Giovanna Rivero (Caravelle)
Tirinea (1969): A Homeland for Bolivian Modernity proposes a reading of this foundational work of the Bolivian post-national phase, written by the “chaqueño” writer Jesús Urzagasti, as an account of melancholia versus alienating modernity. Tirinea is, in fact, the land of “el Chaco” taken to its symbolic limits by a revolutionary imagination. In the residual space of military defeat against Paraguay, Urzagasti writes an illuminating national history and gives life to a different modern subjectivity capable of reformulating old cultural terms in order to consolidate a new Latin American utopia.